Two‐Wave Variable Nanotheranostic Agents for Dual‐Mode Imaging‐Guided Photo‐Induced Triple‐Therapy for Cancer. Issue 27 (2nd August 2022) - Sang, Xiao; Gao, Tong; Liu, Xiaoqing; Shen, Yelong; Chang, Lili; Fu, Shunli; Yang, Han; Yang, Huizhen; Mu, Weiwei; Liang, Shuang; Zhang, Zipeng; Zhang, Na; et al.
Abstract: Photothermal therapy (PTT) is a promising strategy for cancer treatment, but its clinical application relies heavily on accurate tumor positioning and effective combination. Nanotheranostics has shown superior application in precise tumor positioning and treatment, bringing potential opportunities for developing novel PTT‐based therapies. Here, a nanotheranostic agent is proposed to enhance magnetic resonance imaging (MRI)/ near‐infrared fluorescence imaging (NIRFI) imaging‐guided photo‐induced triple‐therapy for cancer. Thermosensitive liposomes co‐loaded with SPIONs/IR780 and Abemaciclib (SIA‐TSLs), peptide ACKFRGD, and click group 2‐cyano‐6‐amino‐benzothiazole (CABT) are co‐modified on the surface of SIA‐TSLs to form SIA‐ α TSLs. ACKFRGD can be hydrolyzed to expose the 1, 2‐thiolamino groups in the presence of cathepsin B in tumors, which click cycloaddition with the cyano group on CABT, resulting in the formation of SIA‐ α TSLs aggregates. The aggregation of SIA‐ α TSLs in tumors enhances the MRI/NIRFI imaging capability and enables precise PTT. Photo‐induced triple‐therapy enhances precision cancer therapy. First, PTT ablates specific tumors and induces ICD via localized photothermal. Second, local tumor heating promotes the rupture of SIA‐ α TSLs, which release Abemaciclib to block the tumor cell cycle and inhibit Tregs proliferation. Third, injecting GM‐CSF into tumor tissue leads to recruitment of dendritic cells and initiation of antitumor immunity. Collectively, these results present a promising nanotheranostic strategy for future cancer therapy. Abstract : A two‐wave variable nanotheranostics strategy is proposed to enhance magnetic resonance imaging/near‐infrared fluorescence imaging dual‐mode imaging‐guided photo‐induced triple‐therapy for cancer. The nanotheranostic agents SIA‐ α TSLs possess the ability of precise localization and light‐controlled drug release, which is beneficial to improve chemo/photo/immuno‐therapeutic efficiency. In general, this unique programmed variable nanotheranostics strategy is expected to achieve precise image‐guided tumor localization therapy.